MODERN METHODS FOR THE VALORISATION OF PROTECTED AREAS IN IAȘI COUNTY. THEIR MONITORING AND MANAGEMENT WITH GIS TECHNOLOGY - Cristina Carmen Stingu (Palici); Valentin Nedeff; Ion Sandu; Petronela Spiridon-Ursu; Silviu Octavian Gurlui; Ioan Gabriel Sandu; Mihaela Orlanda Antonovici (Munteanu); Viorica Vasilache (Acta Geobalcanica, 2020)
The paper presents a series of methods and techniques of investigation used in the valorisation of the special avifaunistic protection areas (SPA), which also integrate historical monuments, included in the list of sites of community importance (SCI) belonging to the Natura 2000 ecological network in Iasi county. One of the analysed aspects consists in monitoring the evolution of their conservation status, which calls for new technological discoveries regarding the instrumental analysis techniques and current methodological systems of processing / operation. The analyses used are those based on the Geographic Information System (GIS), which allow the geographical and cartographic representation of the characteristics contained in the relational databases, making possible the visual representation of the distribution of the natural assets and of the historical monuments in the study areas. The results of these analyses have a special impact on tourism and the development of disadvantaged areas, managing to identify the weaknesses induced by pollution and the anthropic factor.